Virtual Probes of Mineral–Water Interfaces: The More Flops, the Better! - Stack, A.; Gale, Julian; Raiteri, Paolo (the Mineralogical Society of America, 2013)
New approaches are allowing computer simulations to be compared quantitatively with experimental results, and they are also raising new questions about reactivity at mineral–water interfaces. Molecular simulations not only help us to understand experimental observations, they can also be used to test hypotheses about the properties of geochemical systems. These new approaches include rigorous calibration of simulation models against thermodynamic properties and atomic structure. They also encompass rare event theory methods that allow simulation of slow, complex mineral surface reactions. Here, we give an overview of how these techniques have been applied to simulate mineral–water interface structure, growth/dissolution mechanisms, and cluster formation.